A Design and Engineering Methodology for Organization-based simulation model for operating room scheduling problems. (May 2017) - Yahia, Zakaria; Iijima, Junichi; Harraz, Nermine A; Eltawil, Amr B
Most of the current simulation models focus on implementation details without grasping the essence of the system, which makes it difficult to understand the core and the stable part of an enterprise. In this paper, we develop a Design and Engineering Methodology for Organization (DEMO)-based simulation model that combines simulation and the enterprise engineering approach in order to achieve a more holistic view of the enterprise. The four-aspect DEMO models are developed for the operating room scheduling problem, which enabled us to understand the business process from different perspectives. To develop the simulation model, an expanded DEMO with implementation model (DEMO++) is applied. The AnyLogic environment is used for execution. The model evaluates the operational performance of the case mix and master surgery plans that were developed in previous studies. The initial results show the simulation potential in the performance improvement of the operating room system. Furthermore, it makes understanding and exploring the system easier.